G-phase reinforced high-temperature-oxidation-resistant multi-component alloy and preparation process thereof

By controlling the content of Si silicon and Nb niobium and processing, G-phase strengthened high-temperature oxidation resistance multi-component alloy was successfully prepared, which solved the contradiction between the mechanical properties of multi-component alloys and the high-temperature oxidation resistance, and achieved a comprehensive improvement of high strength, benign plasticity and excellent oxidation resistance.

CN119800199AInactive Publication Date: 2025-04-11NANTONG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510033703.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There is a contradiction between the mechanical properties and the high-temperature oxidation resistance of existing multi-component alloys, and it is difficult to improve strength and oxidation resistance at the same time.

Method used

By controlling the content of Si silicon and Nb niobium, the precipitation of G phase is promoted, and combined with vacuum induction smelting, hot rolling, cold rolling, annealing and aging treatment processes, G phase strengthened high-temperature oxidation-resistant multi-component alloy is prepared.

Benefits of technology

It realizes the high tensile fracture strength of the alloy and has good resistance to high temperature oxidation, while maintaining good plasticity, and is suitable for the manufacturing of high-temperature components and corrosion-resistant equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800199A_ABST
    Figure CN119800199A_ABST
Patent Text Reader

Abstract

The invention discloses a G-phase reinforced high-temperature-oxidation-resistant multi-component alloy and a preparation process thereof. The G-phase reinforced high-temperature-oxidation-resistant multi-component alloy is prepared from the following components in percentage by atom: 5.0 to 15.0 percent of Co cobalt, 10.0 to 20.0 percent of Cr chromium, 35.0 to 45.0 percent of Ni nickel, 1.0 to 10.0 percent of Si silicon, 1.0 to 7.0 percent of Nb niobium, 0.01 to 0.03 percent of Nd neodymium and the balance of Fe iron. The preparation method comprises the following steps: according to the atomic percent of various elements in the G-phase reinforced high-temperature-oxidation-resistant multi-component alloy, obtaining the proportion of Co cobalt, Cr chromium, Ni nickel, Si silicon, Nb niobium, Nd neodymium and Fe iron, proportioning, combining into an alloy ingredient, and carrying out vacuum induction melting of heating on the combined alloy ingredient to obtain an alloy melt; and the prepared alloy melt is subjected to casting forming, hot rolling, cold rolling, annealing and aging treatment processes are sequentially conducted, and the G-phase reinforced high-temperature-oxidation-resistant multi-component alloy is obtained. The high tensile breaking strength of the alloy is guaranteed, the excellent high-temperature oxidation resistance of the alloy is also guaranteed, and meanwhile the good plasticity of the alloy is kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material technology, and in particular to a G-phase reinforced high-temperature oxidation-resistant multi-component alloy and a preparation process thereof. Background Art

[0002] Compared with traditional dilute solid solution alloys, multi-component alloys exhibit many excellent properties due to their diversity and adjustability of composition. However, face-centered cubic multi-component alloys generally have the problem of low strength; body-centered cubic multi-component alloys have good strength but poor plasticity. This mismatch between strength and plasticity seriously limits the application of multi-component alloys in engineering. In addition, the good high-temperature oxidation resistance of the alloy can effectively expand its application range in high-temperature environments. Studies have shown that high-strength multi-component alloys generally have poor high-temperature oxidation resistance, while multi-component alloys with excellent high-temperature oxidation resistance usually have low strength and toughness. Therefore, how to simultaneously improve the mechanical properties and high-temperature oxidation resistance of multi-component alloys is of great significance to the future engineering and industrialization of multi-component alloys. Summary of the invention

[0003] Purpose of the invention: In order to overcome the deficiencies in the prior art, the present invention provides a G-phase strengthened high temperature oxidation resistant multi-component alloy and a preparation process thereof, which successfully precipitates more alloy G phases by controlling the content of Si silicon and Nb niobium, thereby ensuring that the alloy has a higher tensile fracture strength, and also ensures the alloy's excellent high temperature oxidation resistance, while maintaining the alloy's good plasticity.

[0004] Technical solution: To achieve the above-mentioned purpose, the present invention provides a G-phase strengthened high-temperature oxidation-resistant multi-component alloy, including a G-phase strengthened high-temperature oxidation-resistant multi-component alloy, wherein the atomic percentage composition of the G-phase strengthened high-temperature oxidation-resistant multi-component alloy is as follows: Co: 5.0-15.0%, Cr: 10.0-20.0%, Ni: 35.0-45.0%, Si: 1.0-10.0%, Nb: 1.0-7.0%, Nd: 0.01-0.03%, and the remaining components are Fe and iron.

[0005] Furthermore, the atomic percentage composition of the G-phase strengthened high temperature oxidation resistant multi-component alloy is: Co: 9.0-11.0%, Cr: 14.0-16.0%, Ni: 39.0-41.0%, Si: 1.5-7.0%, Nb: 1.5-5.0%, Nd: 0.01-0.02%, and the remaining components are Fe.

[0006] Furthermore, the atomic percentage composition of the G-phase strengthened high temperature oxidation resistant multi-component alloy is: Co: 9.0-11.0%, Cr: 14.0-16.0%, Ni: 39.0-41.0%, Si: 3.5-6.0%, Nb: 3.0-4.5%, Nd: 0.01-0.02%, and the remaining components are Fe.

[0007] Furthermore, a preparation process of a G-phase strengthened high temperature oxidation resistant multi-component alloy comprises the following steps:

[0008] Step 1: according to the atomic percentage composition of various elements in the G-phase strengthened high temperature oxidation resistant multi-component alloy, the proportions of Co, Cr, Ni, Si, Nb, Nd and Fe are obtained and proportioned to form an alloy ingredient;

[0009] Step 2: performing vacuum induction melting of the combined alloy ingredients by heating to obtain an alloy melt;

[0010] Step 3: Casting the prepared alloy melt, and sequentially performing hot rolling, cold rolling, annealing and aging treatment processes to obtain a G-phase strengthened high temperature oxidation resistant multi-component alloy.

[0011] Furthermore, the combined alloy ingredients are subjected to vacuum induction melting with heating at a heating rate of not less than 10°C / min, the temperature is raised to 1500°C to 1600°C, and the melting is maintained at this temperature for at least 15 minutes.

[0012] Furthermore, the hot rolling temperature is 1150° C. to 1200° C., and during the hot deformation process, the steel is repeatedly melted and hot rolled again, with a deformation amount of 60% to 70%.

[0013] Furthermore, the cold rolling temperature is 10° C. to 30° C., and the deformation amount is 70% to 80%.

[0014] Furthermore, the annealing is performed by heating the cold-rolled alloy to 1050° C. for annealing for 30 minutes and then cooling.

[0015] Furthermore, the aging treatment is performed at a temperature of 650° C. for 2 hours.

[0016] Beneficial effects: The G-phase reinforced high-temperature oxidation-resistant multi-component alloy and its preparation process of the present invention accurately control the alloy composition, Si silicon and Nb niobium content, successfully promote the precipitation of more G phase, the precipitation of G phase significantly improves the strength of the alloy, and the addition of Si not only promotes the precipitation of G phase, but also forms a SiO2 passivation layer on the alloy surface, improves the high-temperature oxidation resistance of the alloy, and finally achieves the goal of maintaining good or excellent plasticity while improving the strength and high-temperature oxidation resistance of the alloy; adopts vacuum induction melting process, combined with conventional processing techniques such as hot rolling, cold rolling, annealing and aging treatment, the production process is simple and easy, can effectively reduce production costs, and is convenient for industrial promotion and application; can be widely used in the fields of aerospace, energy, chemical industry to manufacture high-temperature components, corrosion-resistant equipment and other parts, can greatly improve the safety and reliability of facilities, reduce equipment maintenance costs, and improve production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The thermodynamic calculation phase diagram of the alloy was obtained for the second set of experiments;

[0018] Figure 2 Scanning images of the alloy microstructure were obtained for the second group of experiments;

[0019] Figure 3 The calculated thermodynamic phase diagram of the alloy was obtained for the seventh set of experiments;

[0020] Figure 4 Scans of the alloy microstructure obtained for the seventh set of experiments. DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with the accompanying drawings.

[0022] A G-phase strengthened high temperature oxidation resistant multi-component alloy comprises a G-phase strengthened high temperature oxidation resistant multi-component alloy, wherein the atomic percentage composition of the G-phase strengthened high temperature oxidation resistant multi-component alloy is as follows: Co: 5.0-15.0%, Cr: 10.0-20.0%, Ni: 35.0-45.0%, Si: 1.0-10.0%, Nb: 1.0-7.0%, Nd: 0.01-0.03%, and the remaining components are Fe and iron.

[0023] Co element plays a role in solid solution strengthening, thereby improving the alloy's long-term strength and creep resistance. In addition, Co can also improve the alloy's hot processing performance, plasticity and impact toughness; Cr element can increase the alloy's resistance to high-temperature oxidation. When the Cr content reaches a critical value, a continuous, dense and well-adhered Cr2O3 oxide film will form on the alloy surface, which protects the alloy from oxidation corrosion. However, the increase in Cr content is bound to enhance the precipitation tendency of the Cr-rich body-centered α-Cr phase in the alloy; Fe element can not only improve the alloy's processing performance but also reduce material costs; Ni element has high chemical stability, is almost not oxidized below 500°C, and can solid dissolve a variety of alloy elements without forming harmful phases; the addition of Si element can promote the surface SiO 2 The formation of the passivation layer hinders the outward diffusion of metal elements and the inward diffusion of oxygen in a high temperature environment. However, when the amount of Si is too high, the continuous thickness of SiO 2 The passivation layer reduces the adhesion of the oxide film.

[0024] Nb element can be used as a solid solution element to strengthen the matrix, and can also form a precipitated phase to strengthen the matrix by fine grain and precipitation. The composite addition of Nb and Si can promote the precipitation of more G phases due to the synergistic effect of Nb and Si. This phase belongs to the hard phase and can effectively improve the strength and hardness of the alloy. However, too much Nb will cause the precipitation of brittle phases at grain boundaries and within the grains, resulting in a sharp decrease in the plasticity of the alloy, which is not conducive to the mechanical properties of the alloy. At high temperatures, too much Nb is oxidized to form Nb2O5. The addition of Nd element can adjust the microstructure of the alloy and improve the mechanical properties because it has a positive effect on the purification of molten steel and the modification of inclusions.

[0025] Through the above analysis of various metal and non-metal raw materials, the atomic percentages of various raw materials are modified, and the atomic percentage composition of the G-phase strengthened high-temperature oxidation-resistant multi-component alloy is: Co cobalt: 9.0-11.0%, Cr chromium: 14.0-16.0%, Ni nickel: 39.0-41.0%, Si silicon: 1.5-7.0%, Nb niobium: 1.5-5.0%, Nd neodymium: 0.01-0.02%, and the remaining components are Fe iron.

[0026] The atomic percentage composition of the G-phase strengthened high temperature oxidation resistant multi-component alloy is: Co: 9.0-11.0%, Cr: 14.0-16.0%, Ni: 39.0-41.0%, Si: 3.5-6.0%, Nb: 3.0-4.5%, Nd: 0.01-0.02%, and the remaining components are Fe.

[0027] A preparation process of a G-phase strengthened high temperature oxidation resistant multi-component alloy comprises the following steps:

[0028] Step 1: according to the atomic percentage composition of various elements in the G-phase strengthened high temperature oxidation resistant multi-component alloy, the proportions of Co, Cr, Ni, Si, Nb, Nd and Fe are obtained and proportioned to form an alloy ingredient;

[0029] Step 2: performing vacuum induction melting of the combined alloy ingredients by heating to obtain an alloy melt;

[0030] Step 3: Casting the prepared alloy melt, and sequentially performing hot rolling, cold rolling, annealing and aging treatment processes to obtain a G-phase strengthened high temperature oxidation resistant multi-component alloy.

[0031] The vacuum induction melting of the combined alloy ingredients is heated at a heating rate of not less than 10°C / min to 1500°C to 1600°C, and the melting is kept at this temperature for at least 15 minutes.

[0032] The hot rolling temperature is 1150°C to 1200°C. During the thermal deformation process, the steel is melted several times and hot rolled again. In order to avoid deformation and cracking during the hot rolling process, the steel is melted several times and hot rolled again. The deformation amount is 60% to 70%.

[0033] The cold rolling temperature is room temperature, about 10° C. to 30° C., and the deformation amount is 70% to 80%.

[0034] For the annealing, the cold-rolled alloy is heated to 1050° C. for 30 min and then cooled to room temperature.

[0035] The aging treatment is performed at a temperature of 650° C. for 2 hours.

[0036] Example

[0037] Too high Si content will reduce the high temperature oxidation resistance of the alloy, too high Nb content will also reduce the high temperature oxidation resistance of the alloy at high temperature, too low Si and Nb content will affect the tensile fracture strength of the alloy, so it is necessary to find a reasonable Si and Nb content to ensure the high temperature oxidation resistance of the alloy and improve the tensile fracture strength of the alloy. Therefore, the vacuum induction melting process is adopted, and when the raw materials are mixed, the raw materials are used in the following nine groups of experiments according to the combination of atomic percentages, and the alloys obtained after the experiment are tested; find the most suitable and the best alloy material ratio; these nine groups of experimental data are shown in Table 1; among them, the three metal materials of cobalt, chromium and nickel have the best atomic percentages of 10.0%, 15.0% and 40.0% respectively, and the best atomic percentage of Nd neodymium is 0.015%; so that only the atomic percentages of Si and Nb are changed.

[0038] Table 1 Atomic percentage of various elements in G-phase strengthened high temperature oxidation resistant multi-component alloy in the experiment

[0039]

[0040] The preparation process of the first group of G-phase strengthened high temperature oxidation resistant multi-component alloys comprises the following steps:

[0041] According to the atomic percentage composition of various elements in the first group of G-phase strengthened high temperature oxidation resistant multi-component alloys, the proportions of Co, Cr, Ni, Si, Nb, Nd and Fe are obtained and proportioned to form the first group of mixed alloy ingredients;

[0042] The combined alloy ingredients are subjected to vacuum induction melting with heating at a heating rate of not less than 10°C / min to a temperature of 1500°C to 1600°C, and the temperature is kept for melting for at least 15 minutes, and a vacuum induction melting process is adopted to obtain an alloy melt;

[0043] The prepared alloy melt is cast and hot rolled, cold rolled, annealed and aged in sequence. The initial hot rolling temperature is 1180°C. In order to avoid deformation and cracking during the hot rolling process, the alloy is returned to the furnace for several times and then rolled again during the hot deformation process, with a deformation amount of 65%. The cold rolling deformation is carried out at room temperature of 10°C to 30°C, with a deformation amount of 75%. The alloy after cold rolling is annealed at 1050°C for 30 minutes and then cooled to room temperature, and then aged at 650°C for 2 hours to obtain the first group of G-phase strengthened high-temperature oxidation-resistant multi-component alloy bars or plates. The tensile fracture strength, elongation at fracture and oxidation of the obtained G-phase strengthened high-temperature oxidation-resistant multi-component alloy material are tested, and the tensile fracture strength is 700MPa and the elongation at fracture is 38%. The weight change after high-temperature oxidation in air at 1000°C for 100 hours is 0.3mg / cm 2 .

[0044] like Figure 1-2 As shown in the figure, the atomic percentage composition of various elements in the second group of G-phase strengthened high temperature oxidation resistant multi-component alloys is obtained, and the proportions of Co cobalt, Cr chromium, Ni nickel, Si silicon, Nb niobium, Nd neodymium and Fe iron are obtained and proportioned to form the second group of mixed alloy ingredients; the subsequent steps are the same as the process steps of the first group, and the second group of G-phase strengthened high temperature oxidation resistant multi-component alloy bars or plates are obtained; and the tensile fracture strength, elongation at fracture and oxidation of the obtained G-phase strengthened high temperature oxidation resistant multi-component alloy material are tested, and the tensile fracture strength is 960MPa, and the elongation at fracture is 37%; the weight change after high temperature oxidation in air at 1000℃ for 100h is 0.2mg / cm 2 .

[0045] The third group of experiments used the same steps as the first group, and the obtained G-phase strengthened high temperature oxidation resistant multi-component alloy had a tensile fracture strength of 1000MPa and a fracture elongation of 35%. The weight change after high temperature oxidation at 1000℃ in air for 100h was 0.18mg / cm 2 .

[0046] The fourth group of experiments used the same steps as the first group, and the obtained G-phase strengthened high temperature oxidation resistant multi-component alloy had a tensile fracture strength of 1030MPa and a fracture elongation of 32%. The weight change after high temperature oxidation at 1000℃ in air for 100h was 0.14mg / cm 2 .

[0047] The fifth group of experiments used the same steps as the first group, and the obtained G-phase strengthened high temperature oxidation resistant multi-component alloy had a tensile fracture strength of 1150MPa and a fracture elongation of 28%. The weight change after high temperature oxidation at 1000℃ in air for 100h was 0.11mg / cm 2 .

[0048] The sixth group of experiments used the same steps as the first group, and the G-phase strengthened high temperature oxidation resistant multi-component alloy obtained had a tensile fracture strength of 1210 MPa and a fracture elongation of 26%. The weight change after high temperature oxidation at 1000°C in air for 100 hours was 0.09 mg / cm 2 .

[0049] like Figure 3-4 As shown in Figure 1, the seventh group of experiments used the same steps as the first group to obtain a G-phase strengthened high temperature oxidation resistant multi-component alloy with a tensile fracture strength of 1270 MPa and a fracture elongation of 22%. The weight change after high temperature oxidation at 1000°C in air for 100 hours was 0.08 mg / cm 2 .

[0050] The eighth group of experiments used the same steps as the first group, and the obtained G-phase strengthened high temperature oxidation resistant multi-component alloy had a tensile fracture strength of 1350MPa and a fracture elongation of 14%. The weight change after high temperature oxidation at 1000℃ in air for 100h was 0.10mg / cm 2 .

[0051] The ninth group of experiments used the same steps as the first group, and the obtained G-phase strengthened high temperature oxidation resistant multi-component alloy had a tensile fracture strength of 740 MPa and a fracture elongation of 21%. The weight change after high temperature oxidation at 1000°C in air for 100 hours was 0.16 mg / cm 2 .

[0052] In the experimental data, the data of the alloys obtained from the first to eighth groups of experiments were compared, and it was found that with the increase of Si silicon and Nb niobium, the tensile fracture strength gradually increased from 700MPa to 1350MPa, but the fracture elongation gradually decreased from 38% to 14%. The weight change of the alloy in the first group after high temperature oxidation at 1000℃ in air for 100h was 0.3mg / cm 2 It shows that its high temperature resistance and oxidation resistance are not high, and its tensile fracture strength is 700MPa, which is too low to meet the actual use of aviation, energy and chemical parts; therefore, Group 1 does not meet the requirements of the better alloy in this scheme, so Group 1 can be abandoned. The tensile fracture strength of Group 8 is 1350MPa, but the elongation at break is reduced to 14%, compared with the elongation at break of 22% in Group 7. The elongation at break of Group 8 is too low, and the weight change after high temperature oxidation in air at 1000℃ for 100h is 0.10mg / cm 2 ; At high temperatures, excessive Nb niobium is oxidized to form Nb 2 O 5 , which is not conducive to the oxidation resistance of the alloy, and when the amount of Si is too high, the continuous thickness of SiO 2 The passivation layer will reduce the adhesion of the oxide film; therefore, the 0.10 mg / cm 2 Compared with 0.08mg / cm in group 7 2 On the contrary, it increases, which is not in line with the actual use of parts in aviation, energy and chemical industries. Therefore, the atomic percentages of Si silicon and Nb niobium selected in the 8th group of experiments were discarded.

[0053] Therefore, the most suitable atomic percentage of Si and Nb is: Si: 1.5%-7.0%, Nb: 1.5%-5.0%. The room temperature tensile fracture strength is not less than 960MPa, and the elongation at break is not less than 22%, showing good strength and plasticity. At the same time, the alloy shows excellent high temperature oxidation resistance. After high temperature oxidation in air at 1000℃ for 100h, the weight change is ≤0.2mg / cm 2 Compared with traditional Cr-containing ferritic steels, such as 12CrMoV, T91, etc., or austenitic stainless steels, such as 304, 316L and 317, G-phase strengthened high-temperature oxidation-resistant multi-component alloys have better high-temperature oxidation resistance.

[0054] In the remaining experiments from the second to the seventh group, we sought a better alloy material ratio, ensuring that the alloy had a high tensile strength while still having a good elongation at break and excellent high temperature oxidation resistance. Therefore, it was stipulated that the tensile strength should not be less than 1000MPa, and the elongation at break should not be less than 25%. At the same time, it was ensured that the alloy had a good high temperature oxidation resistance, which was manifested in that the weight change of the alloy after high temperature oxidation at 1000℃ in air for 100h remained at 0.10mg / cm 2 This standard is the test result standard for alloys obtained by the best alloy material ratio; and the raw material data in the second to seventh groups of experiments were screened. First, the data of Si silicon and Nb niobium in the seventh group of experiments were discarded because their fracture elongation was 22%. This was mainly because too much Nb would cause the precipitation of brittle phases at grain boundaries and within grains, resulting in a sharp drop in alloy plasticity and too low fracture elongation. Therefore, the data of Si silicon and Nb niobium in the seventh group were excluded.

[0055] At the same time, the high temperature oxidation resistance of group 2 and group 3 was compared. After high temperature oxidation at 1000℃ in air for 100h, the weight changes were 0.2mg / cm 2 and 0.18mg / cm 2 , and set excellent high temperature oxidation resistance 0.10mg / cm 2 The difference is too large. In order to obtain the best alloy, the Si silicon and Nb niobium data of the second and third groups were discarded; the tensile fracture strength of the alloys obtained from the experiments of the fourth, fifth and sixth groups finally retained was between 1030MPa-1210MPa, and the elongation at fracture was between 26%-32%. At the same time, the weight change of the alloy after high temperature oxidation at 1000℃ in air for 100h was maintained at 0.09mg / cm 2 -0.14mg / cm 2 The room temperature tensile strength is not less than 1000MPa, and the elongation at break is not less than 25%, reflecting excellent strength and plasticity. The alloy exhibits excellent high temperature oxidation resistance. After high temperature oxidation at 1000℃ in air for 100h, the weight change is maintained at 0.10mg / cm 2 Compared with traditional Cr-containing ferritic steels, such as 12CrMoV, T91, etc., or austenitic stainless steels, such as 304, 316L and 317, the G-phase strengthened high-temperature oxidation-resistant multi-component alloy has better high-temperature oxidation resistance.

[0056] Therefore, the most excellent atomic percentages of Si silicon and Nb niobium are: Si silicon: 3.5-6.0%, Nb niobium: 3.0-4.5%; the atomic percentage of Fe iron changes accordingly, and the atomic percentages of other elements remain unchanged, so that while ensuring that the G-phase strengthened high-temperature oxidation-resistant multi-component alloy has a higher tensile fracture strength, it also ensures a better fracture elongation, so that the alloy has better strength and plasticity, and finally ensures excellent high-temperature oxidation resistance; the alloy's high-temperature oxidation resistance, tensile fracture strength and fracture elongation are simultaneously superior to other conventional alloys; it meets the urgent needs of related fields and has significant practical value.

[0057] Si silicon: 1.5%-7.0%, Nb niobium: 1.5%-5.0%, Fe iron changes accordingly, other elements remain unchanged, this kind of alloy has higher strength, good alloy plasticity and good high temperature oxidation resistance; Si silicon: 3.5-6.0%, Nb niobium: 3.0-4.5%, Fe iron changes accordingly, other elements remain unchanged, this kind of alloy has higher strength while ensuring excellent alloy plasticity and excellent high temperature oxidation resistance; compared with the alloys obtained by the above Si silicon and Nb niobium content, the performance data in all aspects are more excellent.

[0058] At the same time, by comparing the 5th group of experiments with the 9th group of experiments, the addition of Nb niobium and Nd neodymium was reduced in the 9th group of experiments compared with the 5th group of experiments, and the content of Fe iron was added. The obtained alloys were compared, and it was found that the tensile fracture strength of the alloy of the 9th group was much lower than that of the alloy of the 5th group. At the same time, the high-temperature oxidation resistance of the alloy of the 9th group was lower than that of the alloy of the 5th group. Because Nb niobium and Si silicon acted simultaneously inside the alloy to help the precipitation of the G phase, and Nb niobium played a role in fine grain strengthening and precipitation strengthening on the matrix, which can increase the tensile fracture strength of the alloy. Because of the lack of Nb niobium, the tensile fracture strength of the alloy was reduced. At the same time, Nd neodymium can have a positive effect on the purification of molten steel and the modification of inclusions, and adjust the microstructure of the alloy. Purifying the impurities of the alloy can help improve the strength of the alloy. Therefore, the lack of Nd neodymium and the lack of Nb niobium make the tensile fracture strength of the alloy drop rapidly, so that it does not meet the requirements for the tensile fracture strength of the alloy in this scheme.

[0059] like Figure 2 As shown in the figure, in the second group of experiments, Si silicon: 1.5%, Nb niobium: 1.5%, it is shown that the G phase of the alloy melted by the corresponding combination is less, and the G phase of the alloy is in a network shape. The network G phase does not increase the strength of the alloy too much, so the tensile fracture strength of the alloy is 960MPa, as shown in the figure. Figure 4As shown, in the 7th group of experiments, Si silicon: 7.0%, Nb niobium: 5.0%, indicating that the G phase of the alloy melted with the corresponding combination becomes more. In addition to the network G phase in the 2nd group of experiments, a large amount of block or rod-shaped G phase is precipitated to increase the strength of the alloy, so the tensile fracture strength of the alloy is 1270MPa; therefore, it can be seen that with the increase of the atomic percentage of Si silicon and Nb niobium, the coordinated effect of Si silicon and Nb niobium promotes the precipitation of more block or rod-shaped G phase, thereby increasing the tensile fracture strength of the alloy to a higher level.

[0060] The above is only a description of the preferred embodiments of the present invention. Ordinary technicians in this technical field can make several modifications and optimizations based on the above disclosure without departing from the above basic principles. These improvements and optimizations should be regarded as the understood protection scope of the present invention.

Claims

1. A G-phase strengthened high temperature oxidation resistant multi-component alloy, characterized in that: It comprises a G-phase strengthened high temperature oxidation resistant multi-component alloy, wherein the atomic percentage composition of the G-phase strengthened high temperature oxidation resistant multi-component alloy is as follows: Co: 5.0-15.0%, Cr: 10.0-20.0%, Ni: 35.0-45.0%, Si: 1.0-10.0%, Nb: 1.0-7.0%, Nd: 0.01-0.03%, and the remaining components are Fe and iron.

2. The G-phase strengthened high temperature oxidation resistant multi-component alloy according to claim 1, characterized in that: The atomic percentage composition of the G-phase strengthened high temperature oxidation resistant multi-component alloy is: Co: 9.0-11.0%, Cr: 14.0-16.0%, Ni: 39.0-41.0%, Si: 1.5-7.0%, Nb: 1.5-5.0%, Nd: 0.01-0.02%, and the remaining components are Fe.

3. The G-phase strengthened high temperature oxidation resistant multi-component alloy according to claim 1, characterized in that: The atomic percentage composition of the G-phase strengthened high temperature oxidation resistant multi-component alloy is: Co: 9.0-11.0%, Cr: 14.0-16.0%, Ni: 39.0-41.0%, Si: 3.5-6.0%, Nb: 3.0-4.5%, Nd: 0.01-0.02%, and the remaining components are Fe.

4. The process for preparing a G-phase strengthened high temperature oxidation resistant multi-component alloy according to claim 1, characterized in that: The following steps are involved: Step 1: according to the atomic percentage composition of various elements in the G-phase strengthened high temperature oxidation resistant multi-component alloy, the proportions of Co, Cr, Ni, Si, Nb, Nd and Fe are obtained and proportioned to form an alloy ingredient; Step 2: performing vacuum induction melting of the combined alloy ingredients by heating to obtain an alloy melt; Step 3: Casting the prepared alloy melt, and sequentially performing hot rolling, cold rolling, annealing and aging treatment processes to obtain a G-phase strengthened high temperature oxidation resistant multi-component alloy.

5. The process for preparing a G-phase strengthened high temperature oxidation resistant multi-component alloy according to claim 4, characterized in that: The vacuum induction melting of the combined alloy ingredients is heated at a heating rate of not less than 10°C / min to 1500°C to 1600°C, and the melting is kept at this temperature for at least 15 minutes.

6. The process for preparing a G-phase strengthened high temperature oxidation resistant multi-component alloy according to claim 4, characterized in that: The hot rolling temperature is 1150° C. to 1200° C., and during the hot deformation process, multiple remelting and hot rolling are performed again, with a deformation amount of 60% to 70%.

7. The process for preparing a G-phase strengthened high temperature oxidation resistant multi-component alloy according to claim 4, characterized in that: The cold rolling temperature is 10° C. to 30° C., and the deformation amount is 70% to 80%.

8. The process for preparing a G-phase strengthened high temperature oxidation resistant multi-component alloy according to claim 4, characterized in that: For the annealing, the cold-rolled alloy is heated to 1050° C. for annealing for 30 min and then cooled.

9. The process for preparing a G-phase strengthened high temperature oxidation resistant multi-component alloy according to claim 4, characterized in that: The aging treatment is performed at a temperature of 650° C. for 2 hours.